Prevention and Management of Dermatologic Adverse Events Associated With Tumor Treating Fields in Patients With Glioblastoma - Lacouture, Mario E.; Anadkat, Milan J.; Ballo, Matthew T.; Iwamoto, Fabio; Jeyapalan, Suriya A.; La Rocca, Renato V.; Schwartz, Margaret; Serventi, Jennifer N.; Glas, Martin (Frontiers in Oncology, 2020)
Importance: Tumor Treating Fields (TTFields) are an antineoplastic treatment approved for treating newly diagnosed and recurrent glioblastoma, and mesothelioma. TTFields in glioblastoma comprise alternating electric fields (200 kHz) delivered continuously, ideally for ≥18 hours/day, to the tumor bed via transducer arrays placed on the shaved scalp. When applied locoregionally to the tumor bed and combined with systemic temozolomide chemotherapy, TTFields improved overall survival vs temozolomide alone in patients with newly diagnosed glioblastoma. Improved efficacy outcomes with TTFields were demonstrated, while maintaining a well-tolerated and manageable safety profile. The most commonly-reported TTFields–associated adverse events (AEs) are beneath-array dermatologic events. Since survival benefit from TTFields increases with duration-of-use, prevention and management of skin AEs are critical to maximize adherence. This paper describes TTFields-associated dermatological AEs and recommends prevention and management strategies based on clinical trial evidence and real-world clinical experience. Observations: TTFields–associated skin reactions include contact dermatitis (irritant/allergic), hyperhidrosis, xerosis or pruritus, and more rarely, skin erosions/ulcers and infections. Skin AEs may be prevented through skin-care and slight shifting (~2 cm) of array position during changes. TTFields–related skin AE management should be based on clinical phenotype and severity. Depending on diagnosis, recommended treatments include antibiotics, skin barrier films, moisturizers, topical corticosteroids, and antiperspirants. Water-based lotions, soaps, foams, and solutions with minimal impact on electrical impedance are preferred with TTFields use over petroleum-based ointments, which increase impedance. Conclusions: Early identification, prophylactic measures, and symptomatic skin AE management help patients maximize TTFields usage, while maintaining quality-of-life and optimizing therapeutic benefit. Implications for practice: TTFields confer a survival benefit in patients with glioblastoma that correlates positively with duration of daily use. Skin events (rash) are the primary treatment-related AE that can limit duration of use. The recommendations described here will help healthcare professionals to recognize, prevent, and manage dermatologic AEs associated with TTFields treatment. These recommendations may improve cutaneous health and support adherence to therapy, both of which would maximize treatment outcomes.